Punto C/ELE : manual de espanol como lengua extranjera. (Ediciones UC, 2018)
This manual has been prepared to develop the four linguistic skills in Spanish as a foreign language/second language, with a focus on communicative interaction and the production of oral and written texts. It is aimed at students who do not have any knowledge of Spanish and who want to take the step to level A1 of E/LE and teachers who teach that level. Punto C/ELE covers the functional and grammatical content that the Instituto Cervantes Curriculum Plan stipulates for level A1 and is oriented towards knowledge of the Chilean culture, especially for those who study E/LE in an immersion context in Chile or Latin America. Each unit is organized by specific communicative functions associated with specific cultural themes and sociopragmatic uses. In addition, the various topics include listening activities, available in a cloud for easy access by learners and teachers.